Optimization of solid phase microextraction combined with gas chromatography‐mass spectrometry (GC‐MS) to analyze aromatic compounds in fresh tomatoes. Issue 10 (30th April 2019) - Li, Jian; Fu, Yingli; Bao, Xiaolin; Li, He; Zuo, Jinhua
Abstract: In this study, conditions for solid‐phase microextraction coupled to gas chromatography‐mass spectrometry to extract and analyze volatile compounds from fresh tomatoes ( Solanum lycopersicum cv. Fendi) were optimized. Four main experimental parameters were optimized, including internal standard, fiber material coating, extraction temperature, and salt concentration. The optimal extraction conditions were 85 μm Carboxen/Polydimethylsiloxane fiber, 60°C extraction temperature, 1‐heptanol as an internal standard, and without adding sodium chloride in the tomato sample. Analysis of tomato fruit samples using these optimized conditions allowed us to identify 37 volatile compounds that could be grouped into seven categories: aldehydes (11), hydrocarbons (7), alcohols (7), ketones (5), oxygen‐containing heterocyclic compounds (3), esters (3), sulfur‐and nitrogen‐containing heterocyclic compounds (1). Practical applications: In this study, we optimized a method to extract tomato flavor compounds. In recent years, many consumers complained that tomatoes have poor flavor. A method to extract flavor compounds will assist in characterizing the compounds that contribute to tomato flavor and could be used in the development of tomatoes that have enhanced flavor. Abstract : The optimization of solid phase microextraction (SPME) method for tomato was studied and the results showed that the optimal conditions found were 85 μm Carboxen/Polydimethylsiloxane (CAR/PDMS) fiber, the extraction temperature of 60°C, the internal standard of 1‐heptanol, and without sodium chloride addition.